2016
DOI: 10.1108/hff-02-2015-0058
|View full text |Cite
|
Sign up to set email alerts
|

Influence of incidence angle on the aerodynamic characteristics of square cylinders with rounded corners

Abstract: Purpose – The purpose of this paper is to focus on the variation of wake structures and aerodynamic forces with changes in the cylinder corner radius and orientation. Design/methodology/approach – Numerical simulations were performed for flow past a square cylinder with different corner radii placed at an angle to the incoming flow. In the present study, the rounded corner ratio R/D=0 (square cylinder), 0.1, 0.2, 0.3, and 0.4 (where R is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…It was reported that in the case of the cylinder with rounded corners these variations are less significant in comparison with cylinders with sharp corners. [45], Miran and Sohn [46] and Tong and Sparrow [47] investigated the effect of the angle of attack or incidence angle on the flow structure of square cylinders with modified corners. Carassale and Freda [45] investigated the influence of corner modification on the aerody- Some researchers combined the effect of corner modification with other parameters on the wake flow.…”
Section: Corner Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that in the case of the cylinder with rounded corners these variations are less significant in comparison with cylinders with sharp corners. [45], Miran and Sohn [46] and Tong and Sparrow [47] investigated the effect of the angle of attack or incidence angle on the flow structure of square cylinders with modified corners. Carassale and Freda [45] investigated the influence of corner modification on the aerody- Some researchers combined the effect of corner modification with other parameters on the wake flow.…”
Section: Corner Modificationmentioning
confidence: 99%
“…It was reported that rounded corners promote the reattachment of the flow on the lateral faces and as a result the critical angle of incidence was reduced. Miran and Sohn [46] observed that the rounded corner cylinder exhibits a lower critical incidence angle in comparison with the sharp corner square cylinder. Therefore, for R/D = 0 (square cylinder) a critical incidence angle of 12 • was observed whereas for R/D = 0.1-0.4 a value in the range of 5-10 • was reported.…”
Section: Corner Modificationmentioning
confidence: 99%
“…The results indicated that the length of the time-averaged recirculation region was highest for a corner radius ratio of r/D = 0.125. A study on the effect of the angle of incidence on the drag characteristics of a rounded corner square cylinder was presented in [21]. The drag coefficient attained minima when the angle of incidence was between 5 and 10 degrees.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Miran and Sohn (2015) numerically analyzed the effect of rounded corners on the stationary cylinder and found that a rounded corner ratio of approximately R/D = 0.2 -0.3 reduces the drag and lift forces. The influence of the incidence angle was also numerically studied by Miran and Sohn (2016a), who found that rounded corners are a strong function for reduction of aerodynamic forces irrespective of the incoming flow. Kumar et al (2009) used the PIV technique and found that rounded corners significantly influenced the flow features around the bodies.…”
Section: Introductionmentioning
confidence: 99%